Study of somatic cell count variations and hygiene status of dairy cattle - Hachana, Yasser; Tibbini, Ghofrane (Indian Journal of Dairy Science, 2018)
The purpose of this work was to study the main variation factors of somatic cell counts (SCC) in raw milk through the results of milk recording analyses over the last six years, and to try to establish an assessment of the infectious status of the controlled dairy herd. Study was carried out on 253 354 official milk recordings. Somatic cell count was significantly (p< 0.05) influenced by studied factors; season, lactation stage, lactation number and breed. The lowest average SCC was recorded in spring whereas the highest one was recorded in summer. As the cow’s age increases, SCC tends to increase. Cows in first lactation had the lowest average SCC, while cows in 8th and 9th lactation had the highest. Holstein cows exhibited the highest SCC, while brown Swiss and MontbÃ©liarde cows exhibited the lowest one. Based on SCC of raw milk, it was possible to establish an assessment of the infectious status of dairy herd. We could deduce that 47.98% of controlled dairy cows have a SCC less than 300 000 cells/ ml, indicating theyâ€™re mastitis free. Animals with SCC between 300 000 and 600 000 cells/ ml and animals with SCC between 600 000 and 1000 000 cells/ ml represented 17.1 and 11.7% of the controlled herd respectively. Animals with SCC exceeding 1 million cells/ ml represented 23% of total controlled dairy herd, indicating serious clinical mastitis problems. The SCC can be used as an effective tool in monitoring health status of dairy herds and preventing mastitis propagation.